Revising Merger Guidelines: Lessons from the Irish Experience - GORECKI, PAUL K. (ESRI)
Competition authorities typically issue Merger Guidelines setting out the framework within which merger assessment is conducted. Ireland is no exception. The Competition Authority is currently in the process of revising its 2002 Guidelines. In this paper we not only comment on the procedure that is being used to revise these Guidelines as well as the substance of the proposed revisions to the Guidelines, but also draw some wider lessons that might be of assistance to other competition authorities, particularly smaller competition authorities, in revising their Guidelines. The lessons include: carefully distinguishing between proposals for revising the Guidelines that incorporate existing merger assessment custom and proposals that mark a significant departure from current Guidelines as well as existing custom and practice. Proposals for revising the Guidelines, particularly when referring to existing custom and practice, should be specific rather than general; and, if multijurisdictional mergers are important particular attention should be paid to the Guidelines in jurisdictions that are commonly included in such multijurisdictional mergers.
PUBLISHED
Keywords: Ireland; MERGERS; competition; Economics